Composition of Prokaryotic and Eukaryotic Microbial Communities in Waters around the Florida Reef Tract - Peeter Laas; Kelly Ugarelli; Michael Absten; Breege Boyer; Henry Briceño; Ulrich Stingl (Microorganisms, 2021)
The Florida Keys, a delicate archipelago of sub-tropical islands extending from the south-eastern tip of Florida, host the vast majority of the only coral barrier reef in the continental United States. Abiotic as well as microbial components of the surrounding waters are pivotal for the health of reef habitats, and thus could play an important role in understanding the development and transmission of coral diseases in Florida. In this study, we analyzed microbial community structure and abiotic factors in waters around the Florida Reef Tract. Both bacterial and eukaryotic community structure were significantly linked with variations in temperature, dissolved oxygen, and total organic carbon values. High abundances of copiotrophic bacteria as well as several potentially harmful microbes, including coral pathogens, fish parasites and taxa that have been previously associated with Red Tide and shellfish poisoning were present in our datasets and may have a pivotal impact on reef health in this ecosystem.